PCK1 as a potential hub gene in distinguishing lactate metabolism between rheumatoid arthritis and osteoarthritis - Xin,Pengfei; Pei,Shaoqiang; Ma,Nanshan; Xiao,Lianbo (PeerJ, 2025)
Background Lactate is notably involved in the advancement of rheumatoid arthritis (RA) and osteoarthritis (OA). Nevertheless, the causal association between these conditions and lactate remains uncertain. This study aims to use Mendelian randomization (MR) to investigate their relationship with lactate and understand the genetic differences in lactate metabolism between them. Methods Genetic data for RA, OA, and lactate metabolism were obtained from GWAS, GEO, and MSigDB databases. MR analysis was performed using the inverse variance weighted (IVW) method. Differential gene expression analysis was conducted using the “limma” package, and Gene Set Enrichment Analysis (GSEA) was performed with GSEA software. Immune cell infiltration was assessed using the CIBERSORT platform. Validation of differentially expressed genes was carried out via Western blotting. Additionally, weighted gene co-expression network analysis (WGCNA) was employed to identify hub genes, while GO and KEGG analyses were performed to compare mechanistic differences between RA and OA. In vitro experiments were conducted to assess the effects of PCK1 on lactate secretion and cellular functions in RA-FLS. Results MR analysis indicated a causal relationship between RA and OA with lactate levels. Differential gene expression analysis revealed that PCK1 is a key gene underlying the metabolic differences in lactate levels between RA and OA. In vitro experiments demonstrated that knocking down PCK1 in RA-FLS affected lactate secretion, inhibited cell migration, and promoted apoptosis, suggesting its critical role in lactate metabolism. Additionally, GSEA analysis showed significant enrichment of PCK1 in the citrate cycle and gluconeogenesis signaling pathways in RA. Conclusion This study provides genetic evidence supporting the causal relationship between RA, OA, and lactate levels. Additionally, PCK1 is identified as a pivotal target implicated in the metabolic disparities of lactate between RA and OA, highlighting its potential significance in RA therapeutics.
Keywords: Rheumatoid arthritis; Osteoarthritis; PCK1; Lactate metabolism